KAPITAL SOSIAL DALAM PEMBANGUNAN EKONOMI DI KAWASAN TERPENCIL - Anggraeni, Helena; Sugianto, Tjondro (STKIP Persada Khatulistiwa Sintang, 2017)
Abstract: The geographic position of an area should not be a determinant of the economic development in a region. When a region has a low level orbitation to the central government, it is necessary to find alternative capital that is actually embedded in the community and potential to be developed. Rather, the pattern of central development that be applied in a remote area without regard to local condition will only lead to failure. In this case, social capital that can roll out community based development can be a solution especially for people who living in remote area.Keywords: social capital, development communityAbstrak: Posisi geografis dari sebuah kawasan seharusnya bukan merupakan faktor penentu berkembang atau tidaknya pembangunan ekonomi di suatu daerah. Ketika sebuah kawasan memiliki orbit yang rendah terhadap pemerintahan pusat, justru perlu dicari kapital alternatif yang sesungguhnya sudah tertanam di kalangan masyarakat dan potensial dikembangkan. Justru, pola pembangunan dari pusat yang dipaksakan di sebuah daerah tanpa memerhatikan kondisi setempat hanyalah akan membuahkan kegagalan. Dalam hal ini, kapital sosial yang dapat menggulirkan pembangunan berbasis komunitas dapat menjadi solusi khususnya untuk masyarakat yang tinggal di daerah terpencil.Kata Kunci: Kapital Sosial, Komunitas Pembangun